2003
DOI: 10.1038/nrm1228
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation regulates Notch signalling

Abstract: Intracellular post-translational modifications such as phosphorylation and ubiquitylation have been well studied for their roles in regulating diverse signalling pathways, but we are only just beginning to understand how differential glycosylation is used to regulate intercellular signalling. Recent studies make clear that extracellular post-translational modifications, in the form of glycosylation, are essential for the Notch signalling pathway, and that differences in the extent of glycosylation are a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
319
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(324 citation statements)
references
References 118 publications
2
319
0
3
Order By: Relevance
“…The O-fucose glycans of Notch are critical regulators of Notch signaling (49,50). Thus it is important to understand all the factors required for their synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The O-fucose glycans of Notch are critical regulators of Notch signaling (49,50). Thus it is important to understand all the factors required for their synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, however, mutation screening in a series of affected subjects with diverse radiological phenotypes failed to identify any positive cases. LFNG encodes a glycosyltransferase that post-translationally modifies the Notch family of cell surface receptors, a key step in the regulation of this signaling pathway (Haines and Irvine, 2003). The LFNG protein is a fucose-specific ␤-1,3-N-acetylglucosaminyltransferase (Bruckner et al, 2000;Moloney et al, 2000) that functions in the Golgi to post-translationally modify the Notch receptors, altering their signaling properties (Haines and Irvine, 2003).…”
Section: Lunatic Fringementioning
confidence: 99%
“…LFNG encodes a glycosyltransferase that post-translationally modifies the Notch family of cell surface receptors, a key step in the regulation of this signaling pathway (Haines and Irvine, 2003). The LFNG protein is a fucose-specific ␤-1,3-N-acetylglucosaminyltransferase (Bruckner et al, 2000;Moloney et al, 2000) that functions in the Golgi to post-translationally modify the Notch receptors, altering their signaling properties (Haines and Irvine, 2003). Earlier studies have shown that Lfng gene expression is severely disregulated in Dll3-null mice, suggesting that Lfng expression is dependent on Dll3 function Kusumi et al, 2004).…”
Section: Lunatic Fringementioning
confidence: 99%
“…In particular, the structure of accessible carbohydrates present at the cell surface is part of the cell 'glycome' and is determined by the coordinated expression of genes including glycosyltransferases, glycosidases and nucleotide-sugar transporters. These enzymes and transporters participate in the functional regulation of a number of other proteins and receptors, such as members of the Wnt and Notch families, galectins, membrane lectins or selectins, whose activities are dependent upon their glycosylation or the glycosylation of their ligands [1][2][3]. Glycosaminoglycans (GAGs) constitute a specific type of glycans of major importance since, depending upon their nature, electrostatic charge and abundance, they modulate the locally available concentrations of various intercellular mediators in the vicinity of the cell surface.…”
Section: Introductionmentioning
confidence: 99%